TRAINING ON MAKING TYPICAL ACEH CAKE FOR MOTHERS OF PKK VILLAGE TUMPOK TEUNGOH LHOKSEUMAWE CITY - Teuku Alfiady; Arinanda; Rizka Nurlaila; Ainol Mardhiah; Erna Isfayani; Rini Julistia (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
Training on making typical Acehnese cakes was held as a form of contribution in improving the competence of individuals and community groups, especially PKK mothers, Teumpok Teungoh village, Banda Sakti sub-district, Lhokseumawe City. The purpose of this service activity is not only to provide additional knowledge specifically for mothers who have free time, provide opportunities to be independent with home businesses but do not have skills, but also to build relationships with local residents. With this service, it is hoped that the participants can run a traditional cake business independently or in groups so that they can contribute to meeting family needs. This series of assistance also includes business management administration assistance,; repair of business premises, and training in making typical Acehnese cakes with various traditional cakes.